2015
DOI: 10.1007/s00221-015-4208-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroelectric adaptations to cognitive processing in virtual environments: an exercise-related approach

Abstract: Recently, virtual environments (VEs) are suggested to encourage users to exercise regularly. The benefits of chronic exercise on cognitive performance are well documented in non-VE neurophysiological and behavioural studies. Based on event-related potentials (ERP) such as the N200 and P300, cognitive processing may be interpreted on a neuronal level. However, exercise-related neuroelectric adaptation in VE remains widely unclear and thus characterizes the primary aim of the present study. Twenty-two healthy pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…The application of VR to sport has taken many forms, with various types of sport tasks, VR technologies, and types of athletes used in the research. Some researchers have examined questions relating to the use of VR technology itself, such as comparing outcomes when using VR and not using VR (e.g., Annesi and Mazas 1997;Legrand et al 2011;Mestre et al 2011;Plante et al 2003a), the effects of immersion in the virtual environment (Ijsselsteijn et al 2004;Vogt et al 2015), and differences between computer-controlled and real virtual competitors (Snyder et al 2012). In contrast, other researchers have used VR technology as part of a methodology to answer more general questions about factors related to sport performance.…”
Section: A Conceptual Framework For the Application Of Virtual Realitmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of VR to sport has taken many forms, with various types of sport tasks, VR technologies, and types of athletes used in the research. Some researchers have examined questions relating to the use of VR technology itself, such as comparing outcomes when using VR and not using VR (e.g., Annesi and Mazas 1997;Legrand et al 2011;Mestre et al 2011;Plante et al 2003a), the effects of immersion in the virtual environment (Ijsselsteijn et al 2004;Vogt et al 2015), and differences between computer-controlled and real virtual competitors (Snyder et al 2012). In contrast, other researchers have used VR technology as part of a methodology to answer more general questions about factors related to sport performance.…”
Section: A Conceptual Framework For the Application Of Virtual Realitmentioning
confidence: 99%
“…The virtual environment is typically displayed on computer screens or projected against a wall. A larger display or the inclusion of more multimodal elements of the environment will increase the sense of immersion in the virtual world (Vogt et al 2015) and this can influence performance. Using a more immersive virtual environment during a cycling task (i.e., showing the track from the point of view of the rider versus from a birds eye view) has increased motivation and the speed of cycling in participants (Ijsselsteijn et al 2004).…”
Section: The Virtual Reality Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity is related to changes in the brain through overall cardiovascular conditioning, and it enhances cerebral blood flow and oxygen supply to neurons [33]. Chronic exercise is found to be associated with an improvement in spatial memory and positive cholinergic effects [17]. In any case, it is apparent that even a single bout of moderate intensity exercise can bring about an improvement in cognition, and we believe that this is very important, as aerobic exercise could have a dual benefit, both for physical and mental health [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…However, the existing literature has demonstrated that specific task and intensity of task induce fatigue, which in turn influences the performance [13][14][15]. Further neurophysiological studies support a possible role of fatigue in mediating many of the behavioral effects associated with cognitive performance [16,17].…”
Section: Introductionmentioning
confidence: 99%